Pengaruh Eksrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) Terhadap Pertumbuhan Bakteri Streptococcus pyogenes Secara In Vitro - Yuliana Prasetyaningsih; Eni Kurniati; Dina Setiarini (Journal of Health (JoH), 2017)
Background: Infectious diseases are diseases caused by pathogenic bacteria such as Streptococcus pyogenes bacteria. This bacterium is a gram-positive, cocci-shaped chain that infect the respiratory tract. As a result of irrational use of antibiotics is causing bacterial resistance. Utilization of plants used in traditional medicine as an alternative by some people. Binahong (Anredera cordifolia (Ten.) Steenis) is a plant that can be used as a traditional medicine can be found easily in Indonesia. Binahong is one of the medicinal plants are thought to have antibacterial effects. Objective: To investigate the effect of leaf extracts binahong (Anredera cordifolia (Ten) Steenis) against Streptococcus pyogenes bacterial growth in vitro. Research Methods: The study was conducted in July 2014 in the Laboratory of Bacteriology of Ministry of Health polytechnic Yogyakarta. Types experimental research is real by using desain one-short case study. Binahong leaves were tested came from Yogyakarta Sleman. Analysis of the data obtained and performed descriptive statistics and presented in tables or graphs. The statistical test used is one way analysis of variance (One Way Anova). Result: The mean diameter of inhibition zone binahong leaf extract on the growth of the bacterium Streptococcus pyogenes at the smallest concentration that is 20% of 12.3 mm and largest concentration of 100% at 23.6 mm. Conclusion: there is influence binahong leaf extract against Streptococcus pyogenes growth in vitro.